Feasibility and safety of continuous retrograde administration of Del Nido cardioplegia: a case series. Issue 1 (December 2015) - Najjar, Marc; George, Isaac; Akashi, Hirokazu; Nishimura, Takashi; Yerebakan, Halit; Mongero, Linda; Beck, James; Hill, Stephen; Takayama, Hiroo; Williams, Mathew
Abstract Background Del Nido (DN) cardioplegia, a calcium-free, hyperkalemic solution containing lidocaine and magnesium has been developed to help reduce intracellular calcium influx and the resulting myocyte damage in the immediate postischemic period following cardiac arrest. DN cardioplegia has been used for pediatric cardiac surgery but its use in complex reoperative surgery has not been studied. We specifically report the outcomes of patients undergoing reoperative cardiac surgery after previous coronary artery bypass grafting with a patent internal mammary artery (IMA). Methods Patients undergoing reoperative cardiac surgery with prior coronary bypass grafting surgery were studied between 2010 and 2013. Fourteen patients were identified who required continued retrograde cardioplegia administration. In all cases, an initial antegrade dose was given, followed by continuous retrograde administration. Demographics, co-morbidities, intra-operative variables including cardioplegia volumes, post-operative complications, and patient outcomes were collected. Results The mean age of all patients was 73.3+/−6.7 years, and 93 % were male. Aortic cross clamp time and cardiopulmonary bypass times were 81+/−35 and 151+/−79 mins, respectively. Antegrade, retrograde and total cardioplegia doses were 1101+/−398, 3096+/−3185 and 4367+/−3751 ml, respectively. An average of 0.93+/−0.92 inotropes and 1.50+/−0.76 pressors were used on ICU admission after surgery. ICU and total hospital lengths of stay were 5.5+/−7.4 and 9.6+/−8.0 days, respectively. Complications occurred in two patients (14 %) (pneumonia and prolonged mechanical ventilation) and new arrhythmias occurred in five patients (36 %) (four new-onset atrial fibrillation and one pulseless electrical activity requiring 2 min of chest compression). No perioperative myocardial infarctions were noted based on electrocardiograms and cardiac serum markers. Postoperatively, left ventricular function was preserved in all patients whereas two patients (14 %) had mild decrease in right ventricular function as assessed by echocardiography. No mortality was observed. Conclusion Del Nido cardioplegia solution provides acceptable myocardial protection for cardiac surgery that requires continuous retrograde cardioplegia administration. DN cardioplegia's administration in a continuous retrograde fashion with a patent IMA is believed to provide adequate myocardial protection while avoiding injuring the IMA through dissection and clamping.